Development of environmental change teaching materials based on the local context of Kayu Agung - Anisa Aprilia; Nike Anggraini; M. Meilinda (Research and Development in Education (RaDEn), 2026)
Background-To date, locally contextualized teaching materials on environmental change specific to Kayu Agung have not been developed; therefore, this study aims to address this gap while enhancing students’ environmental awareness through context-based learning. Objective- This study aims to develop teaching materials on environmental change integrated with the local contextual realities of Kayu Agung for Grade X high school students. Method- The research employed a development design using the ADDIE model, limited to the analysis, design, and development stages. Data collection techniques included validation sheets, student response questionnaires, and interviews. The validation process was conducted by two material experts, while a small-group trial involved 10 Grade X students from Kayu Agung 1 Public High School. Results- The validation results indicated that the developed teaching materials were categorized as very feasible, with a percentage score of 92%, while the practicality test results from students were categorized as very practical, with a percentage score of 90%. Conclusion-The environmental change teaching materials integrated with the local context of Kayu Agung are considered feasible and practical for use in learning and have the potential to enhance students’ environmental awareness.